Control of hip reduction with dysplastic development while using splinting abduction - José Julio Requeiro Molina; Ana María Machado Consuegra; Leobys Kautets Pardiñas de León; Liyanira Alonso Leiva; Juana María Morejón Fernández; Gabriela María Requeiro Molina (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
The success of hip with dysplastic development treatment is related to the early diagnosis and the treatment used. Orthotic treatment should guarantee the remodeling of the dysplastic hip, for which it is necessary to comply with hip flexion and abduction requirements in adequate degrees to avoid the appearance of complications. Radiographic study is a way to corroborate that these requirements are met in patients´ pelvis with the orthotic device placed, to whose resulting image three measurements are made. The case images of a four months female patient, with clinical and radiographic signs of dysplastic hip development are presented, in order to show the appropriate degrees of flexion that the orthosis should provide. The application of these methods offers greater certainty about the reduction achieved and guarantees the joint remodeling toward normality in the hip with dysplastic development.